2008
DOI: 10.1111/j.1755-5949.2008.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Ang II and Ang IV: Unraveling the Mechanism of Action on Synaptic Plasticity, Memory, and Epilepsy

Abstract: The central angiotensin system plays a crucial role in cardiovascular regulation. More recently, angiotensin peptides have been implicated in stress, anxiety, depression, cognition, and epilepsy. Angiotensin II (Ang II) exerts its actions through AT(1) and AT(2) receptors, while most actions of its metabolite Ang IV were believed to be independent of AT(1) or AT(2) receptor activation. A specific binding site with high affinity for Ang IV was discovered and denominated "AT(4) receptor". The beneficiary effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 249 publications
(395 reference statements)
1
36
0
Order By: Relevance
“…Initial studies of a research group suggested anti-convulsant actions of Ang peptides against pentylenetetrazol-induced seizures [244] reviewed recently [245]. Emerging new data, however, suggest a more complex effect of angotensins on seizure activity [246]. The anti-convulsant action of AngIV has been confirmed in the pilocarpine model of epilepsy [247].…”
Section: Angiotensinsmentioning
confidence: 82%
“…Initial studies of a research group suggested anti-convulsant actions of Ang peptides against pentylenetetrazol-induced seizures [244] reviewed recently [245]. Emerging new data, however, suggest a more complex effect of angotensins on seizure activity [246]. The anti-convulsant action of AngIV has been confirmed in the pilocarpine model of epilepsy [247].…”
Section: Angiotensinsmentioning
confidence: 82%
“…These observations have long encouraged the notion that AngIV-based pharmaceuticals may have potential as antidementia therapeutics (Mustafa et al, 2001;von Bohlen und Halbach, 2003;Gard, 2004Gard, , 2008De Bundel et al, 2008;Wright and Harding, 2010). The transformation of AngIV and earlier described analogs into clinically useful agents has been impeded by their lack of metabolic stability and inability to penetrate the blood-brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, AngIV-based pharmaceutical agents have been suggested as antidementia therapeutic agents (Mustafa et al, 2001;von Bohlen und Halbach, 2003;Gard, 2004Gard, , 2008De Bundel et al, 2008;Wright and Harding, 2008). Despite promising behavioral effects in animal models of dementia, two critical physiochemical properties, namely lack of metabolic stability and inability to penetrate the blood-brain barrier (BBB), have precluded drug development.…”
Section: Introductionmentioning
confidence: 99%